PEMIDANAAN ANAK DALAM KECELAKAAN LALU LINTAS ( STUDI KASUS DI KABUPATEM BANYUANGI ): CHILD VICTIMIZATION IN TRAFFIC ACCIDENTS (CASE STUDY IN BANYUWANGI REGENCY) - Lailatul Fitria; Dwi Hastuti (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Law Number 22 of 2009 concerning Road Traffic and Transportation aims to improve public welfare and ensure safety and smooth traffic flow. However, problems arise when minors are involved in traffic accidents that result in fatalities. Two cases in Banyuwangi have drawn attention: Okta, a student who hit a man while on his way to school, and Marstelysia Denasya, who was involved in an accident on February 16, 2023, on the Banyuwangi–Jember Highway. This study formulates two main questions: how is the process of handling minors in traffic violations that lead to death carried out, and what is the criminal responsibility of minors in such cases? The research method used is empirical, combining sociological, legislative, and phenomenological approaches. The study shows that both cases were not brought to court. The handling was based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Supreme Court Regulation Number 4 of 2014, emphasizing the principle of restorative justice. The resolution process was conducted transparently, accountably, and in an integrated manner, by bringing together the victim and the perpetrator in a forum to engage in dialogue and seek a mutual solution. This approach is considered more appropriate for dealing with legal violations committed by minors, while still taking into account legal and humanitarian aspects. Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan bertujuan meningkatkan kesejahteraan masyarakatserta menciptakan keselamatan dan kelancaran lalu lintas. Namun, persoalan muncul ketika anak di bawah umur terlibat dalam kecelakaan lalu lintas yang menyebabkan kematian. Dua kasus di Banyuwangi menjadi sorotan: Okta, seorang pelajar yang menabrak seorang pria saat berangkat sekolah, dan Marstelysia Denasya yang mengalami kecelakaan pada 16 Februari 2023 di Jalan Raya Banyuwangi– Jember. Penelitian ini merumuskan dua pertanyaan utama: bagaimana proses penanganan anak dalam pelanggaran lalu lintas yang menyebabkan kematian, dan bagaimana pertanggungjawaban pidana anak di bawah umur dalam kasus tersebut. Metode penelitian yang digunakan adalah empiris, dengan pendekatan sosiologis, perundangundangan, dan fenomenologis. penelitian menunjukkan bahwa kedua kasus tidak dilanjutkan ke pengadilan. Penanganan dilakukan berdasarkan Undang-Undang No. 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak dan Peraturan Mahkamah Agung No. 4 Tahun 2014, dengan mengedepankan prinsip restorative justice. Proses penyelesaian dilakukan secara transparan, akuntabel, dan terpadu, dengan mempertemukan korban dan pelaku dalam satu forum untuk berdialog dan mencari solusi bersama. Pendekatan ini dianggap lebihsesuai dalam menangani pelanggaran hukum oleh anak di bawah umur, dengan tetap mempertimbangkan aspek hukumdan kemanusiaan